A fundamental study on the implementation of telecenter - Naharu, Nasrah; Ung, Ling Ling; Saibin, Tammie Christy (2016)
ICT plays an important role in rural development especially in improving their socio economy. Many developing countries are struggling in the initiatives to reduce ICT gap between rural and urban community, causing the rural community unable to escape from poverty. The main purpose of this research is to review the success factors of telecenter implemented in many countries. This will be carried out based on paper review of scientific literature published in different databases. Later, a telecenter in Sabah with be used as a case study in this research, to study its effectiveness and how it has changed the community life in positive way. The model and framework of the telecenter will be identified to see the effectiveness in terms of their success factors and weaknesses. The findings will benefit researchers who intend to start telecenter in rural area and also furnish the government with the ICT needs of rural community.